Study the Incidence of Fistula- in- Ano in Subsequent to Anal Abscess - Kareem Dhahir , Nasir (Diyala Journal of Medicine, 2020)
Background: The Fistula disease is considered common surgical case in the surgical wards of the Baquba teaching hospital, and consider as a complication of the anorectal abscess. Objective: To investigate the incidence of cases that infect with fistula in ano in subsequent to different types of anorectal abscesses. Patients and Methods: This study performed in the Baquba teaching hospital in a period from January 2016 until Jun 2018 including 216 patients (124 male and 92 female); all patients were included in the study . Samples of the patients classified into three groups according to the type of management. Results: The results show that the high incidence of fistula in ano is appearing in patients associated with hemorrhoids 8.84%, and high percent in patients who had a perianal abscess (63.48%) Regarding the distribution of cases according to age and sex, a low percentage of cases appear in age (1-10) with 6.45% and 2.18% in males and females respectively. While the highest percentage appears in the males at age (21-30) with 37.11% and in females is at the age (11-20) with 29.35%. And by the chi-square value for males is 16.37 and for females is 9.94 in a significant value of p=0.01 and p=0.05 respectively. Conclusion: Fistula in ano can be associated with cases have hemorrhois, and more present with patients who have a perianal abscess, and the early drainage of the abscess can prevent development of the fistula.